(untitled) (American Journal of Islam and Society, 2011)
This book looks like a serious academic study in Islamic theology. It is divided into nine chapters that build on an overall argument and has a great number of endnotes, quoting Muslim sources and literature pro-duced in the field of Islamic studies. The book’s author works with-in Washington’s circle of government institutions and think tanks. His book comes with a foreword and no fewer than ten endorsements by colleagues of Reilly, which praise his erudition, insight, and abil-ity to analyze and explain the Muslim mind. I wonder whether they were all aware that the book they endorsed is, in fact, a Catholic refutation of Ashʿarite Muslim theology, the leading branch of Sunni theology. However, Reilly exempts Shiite theology from his harsh criticism ...